Governance for sustainability, a matter of science and ethics. Issue 9 (20th October 2016) - Frank, Hartmut
Abstract : The chemical sciences, as other natural science disciplines, and their technological-industrial applications have relieved mankind from the limitations of the natural environment and from the continuous struggle for fulfillment of daily basic needs. This has resulted in an unprecedent- in a material sense- almost luxurious life style for most living in modern industrialized societies. The power and efficiency of the scientific-technical paradigm is so great that it appears achievable to ascertain such basic welfare globally. Evidently, the modern problem of sustainability is a question of learning how to reach higher levels of applied professional ethics, of responsibility and care for the common good. Rather than wasting industrial capabilities in an egotistic capitalist approach of continuous material exploitation, and expansion on the same (horizontal) level, the enormous enthalpy (or profit) gleaned from such mature state of science and technology should be invested to start growing in a (vertical) direction to higher levels of mutuality and consciousness: largely a matter of education for advancing towards a higher cultural level.